Parties and party systems : structure and context - Johnston, Richard, 1948-; Sharman, Campbell (UBC Press, 2015)
Party systems. Party organization. For too long, scholars researching in these two areas have worked in isolation. This book bridges the divide by bringing together political scientists from both traditions to examine the intersection of rules, society, and the organization of parties within party systems. Blending theory and case studies, Parties and Party Systems builds upon the work of R. Kenneth Carty to examine how parties weather the organizational challenge of appealing to a dispersed membership while maintaining a degree of central direction. This volume will provoke theoretical reconsideration and inspire research at the organization-system nexus.